2007
DOI: 10.1088/0964-1726/16/5/021
|View full text |Cite
|
Sign up to set email alerts
|

The performance of magnetorheological fluid in squeeze mode

Abstract: Abstract. In a magnetorheological (MR) fluid, the rheological properties can be changed in a controlled way, the changes being reversible and dependent on the strength of a magnetic field. The fluids have potentially beneficial applications when placed in various geometrical arrangements. The squeeze mode is a geometric arrangement where two flat parallel solid surfaces, facing each other, are pushed towards each other by an external force, operating at right angles to the surfaces. The liquid initially in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 21 publications
7
70
2
Order By: Relevance
“…A field dependence of H 0.91 was found for compression in contrast to the H 1.4 dependence observed under shearing. Constant area squeeze flow MR experiments were carried out by Mazlan et al (2007Mazlan et al ( , 2008. More recently, Gstöttenbauer et al (2008) designed a test rig to explore the flow behavior of MR fluids under sinusoidal loading modes.…”
mentioning
confidence: 99%
“…A field dependence of H 0.91 was found for compression in contrast to the H 1.4 dependence observed under shearing. Constant area squeeze flow MR experiments were carried out by Mazlan et al (2007Mazlan et al ( , 2008. More recently, Gstöttenbauer et al (2008) designed a test rig to explore the flow behavior of MR fluids under sinusoidal loading modes.…”
mentioning
confidence: 99%
“…The studies exploring MR fluids in the squeeze mode and the involved phenomena are but a few. For example, (Mazlan et al, 2007;Farjoud at al., 2009a, b) revealed that MR fluids can provide a much larger range of controllable force in small operational envelopes compared to flow and direct shear modes. Systematic investigation of MR fluids reported in squeeze mode research described in (Mazlan et al, 2012) showed that the fluids experienced rheological changes in three stages during compression and tension and that fluid-particles separation phenomenon was the main cause of the unique behaviour of MR fluids.…”
Section: Fig 2 Illustration Of Mr Fluid Clumping Behaviourmentioning
confidence: 99%
“…The basic properties and behaviour of MR fluid in shear mode actuation and damping are completely studied and reported [37][38][39][40]. The most powerful mode of operation of MR fluid is squeeze mode but relatively not much literature is reported [41,42]. The behavior of MR fluid is commonly represented as a Bingham -Plastic model having a variable yield stress τy, depending on the magnetic field H Where τ y (H) is the magnetic field dependent shear mode yield stress of the MR fluid, µ is the fluid viscosity and γ is the shear rate.…”
Section: Characteristics Of Mr Fluidmentioning
confidence: 99%